Lời giải
Đáp án đúng là: D
\(\frac{{x + 3y}}{{4x + 8y}}\,\,.\,\,A = \frac{{{x^2} - 9{y^2}}}{{x + 2y}}\)
\(A = \frac{{{x^2} - 9{y^2}}}{{x + 2y}}:\frac{{x + 3y}}{{4x + 8y}}\)
\( = \frac{{\left( {x - 3y} \right)\left( {x + 3y} \right)}}{{x + 2y}}:\frac{{x + 3y}}{{4\left( {x + 2y} \right)}}\)
\( = \frac{{\left( {x - 3y} \right)\left( {x + 3y} \right)}}{{x + 2y}} \cdot \frac{{4\left( {x + 2y} \right)}}{{x + 3y}} = 4\left( {x - 3y} \right)\).
Tìm giá trị của x để phân thức A chia hết cho phân thức B biết:
\(A = \frac{{{x^3} - {x^2} - x + 11}}{{x - 2}};\,\,B = \frac{{x + 2}}{{x - 2}}\).
Cho\(A = \frac{{{x^2} + {y^2} + xy}}{{{x^2} - {y^2}}}:\frac{{{x^3} - {y^3}}}{{{x^2} + {y^2} - 2xy}}\)và \(B = \frac{{{x^2} - {y^2}}}{{{x^2} + {y^2}}}:\frac{{{x^2} - 2xy + {y^2}}}{{{x^4} - {y^4}}}\).
Khi x + y = 5 hãy so sánh A và B.